Alternatives to in-person exercise classes and training in Germany during the first COVID-19 lockdown - Füzéki, E.; Fischer, M.; Würzberger, L.; Groneberg, D. A.; Banzer, W. (Health Promotion International, 2021)
COVID-19 containment efforts in most countries included temporary closure of all non-essential services, such as sports and exercise facilities. Also in Germany, sports clubs (SC) had to close for about 2 months starting mid-March 2020. The aim of the present study was to assess what alternatives German SC developed to in-person exercise classes and training. We conducted an anonymous online survey among large German SC. Invitation was sent to 178 SC, 61 data sets could be analyzed. A total of 92% of SC have offered alternatives to in-person exercise classes and training, most of which were digital. Reasons for not offering any alternatives were the lack of financial, personal or technical resources. The large majority (82.1%) of the SC have also allowed non-club members free access to digital alternatives, and 69.6% considered keeping this freely accessible even after the restrictions have been lifted. Almost three quarters (72.3%) of the sport clubs have received no support from their regional umbrella sports organization. In light of the dynamic development of the COVID-19 pandemic, SC must be prepared to offer alternatives to in-person exercise classes and training also on the middle term. These efforts should be supported by sports organizations and communities.